Stabilized oxygen vacancies over heterojunction for highly efficient and exceptionally durable VOCs photocatalytic degradation - Sun, Minghui; Wang, Xiaoguang; Chen, Zhiquan; Murugananthan, Muthu; Chen, Yong; Zhang, Yanrong (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Enrichment of OVs on the BiVO4 component of R-BiVO4/WO3/TNTs composite matrix by a simple electrochemical reduction step.•Achievement of enhanced electron-hole separation and charge transport capabilities by introducing OVs in R-BiVO4/WO3/TNTs.•Improving the reaction stability of OVs by transforming active species OH into O2− during the photocatalytic process.•R-BiVO4/WO3/TNTs that exhibit 28 times higher photocurrent density and a highly efficient VOCs photocatalytic degradation. In this study, an electrochemical reduction strategy was adopted to introduce oxygen vacancies (OVs) into BiVO4/WO3/TiO2 nanotubes composite film (R-BiVO4/WO3/TNTs), and the newly generated OVs were mainly distributed on BiVO4. Desired concentration and distribution of the OVs were achieved by optimizing the reduction potential and duration. By introducing the reduced BiVO4, the inherent reaction mechanism dominated by OH and photogenerated hole was changed into the reaction dominated by O2− and hole, thereby improving the stability of the OVs in the catalytic process. The construction of heterojunction with the stabilized OVs had a significant contribution towards charge carrier separation and transmission in the material, and especially the stability of the performance. Thus, the R-BiVO4/WO3/TNTs exhibited a 28 times higher photocurrent intensity than the pristine BiVO4/WO3/TNTs, and the one-time purification experiment further confirmed the excellent performance and persistent nature of R-BiVO4/WO3/TNTs composite film in the actual treatment of VOCs.